Common psychiatric centities and clinical perspectives in time of crisis - Vargas-Murga, Horacio (2024)
This article reviews common psychiatric entities and clinical perspectives during times of crisis, analyzing their impacton mental health. Crises, categorized as pandemics, natural disasters, armed conflicts, and economic crises, significantlyincrease the prevalence of mental disorders and exacerbate preexisting conditions, posing challenges to the outreach andpossibilities of mental health systems. The COVID-19 pandemic, for instance, has led to increased psychiatric hospitalizationsamong children and adolescents due to excessive use of digital media. The article analyzes several psychiatric disorders, suchas psychoses, mood, anxiety, sleep, eating, obsessive-compulsive, and stress-related disorders, describing their definitions,symptoms, risk factors, impacts during crises, and treatment strategies. It highlights the importance of social support inmitigating the negative effects of crises on mental health, recommending solid community networks and accessible mentalhealth services. Additionally, it suggests integrating technology, such as mobile applications and telemedicine, to providepsychological support and treatment during crises. The need for a multidimensional and adaptive approach for themanagement of psychiatric disorders is emphasized, promoting a more effective and resilient response from the mental healthsystem. The importance of strengthening these systems and developing adaptive therapeutic strategies to address emergingneeds in times of crisis is also remarked.